Exploring the relationship between gender-differentiated land rights and climate change adaptation for food security in Western Kenya - Etale, Linda Sarah Mutesi (My University, 2020)
This study argues that gendered-land rights majorly undermine efforts towards sustainable food security within households amid adverse changes in climate. Women’s contribution to adaptation is also acknowledged despite the existing challenges of insecure access to land. Secure access to land alone is not a guarantee to food security within the context of changing climate. This being the case, this study aimed to investigate whether increased access to land could be a starting point towards equipping households with a tool (land) to begin the process of practicing sustainable agriculture for food security. The study sites were in Kenya where land is predominantly owned and controlled by men, with women majorly accessing it through male relations. The vulnerability of female-headed households to the effects of climate change and resultant food insecurity where their land rights had been denied, was also explored. The study examined policy and legal frameworks that protect women’s land rights in light of the predominant cultural practices, increased climate change and food insecurity episodes. In addition, the study explored practices that women engaged in towards adaptation and meeting the food security needs of households. Ultimately, the study examined the relationship between land access, climate change, and food security. This is in addition to identifying strategies that women can use in response to land rights challenges, to build resilience to climate change and achieve food security. Lastly, the study identified strategies that can be applied to protect vulnerable women’s land rights. This study used a descriptive research design to conduct a cross-sectional study in Matungu and Mumias East sub-counties in Kakamega County, in western Kenya. The research design is feminism, and data were collected through review of literature, focus groups, key-informant interviews and questionnaires. Through this approach the study allowed respondents including farmers, Government officials, NGO representatives, and other professionals to give their experiences concerning climate change, adaptation, food security, and women’s land rights. The study makes a contribution to initiatives targeted at creating sustainable solutions in adaptation for food security in Kenya and Sub-Saharan Africa. The study found that despite having a robust legal framework that addresses land rights injustices, Kenya still grapples with competing customs and practices that seemingly undermine efforts towards adaptation. Patriarchy still predominantly informs actions that mostly disfavor women in terms of rights to the capital of production yet they are a major contributor to labor and knowledge in agriculture development. The study recommends strategies that can be used to inform policy and practice towards the true transformation of communities in terms of livelihood development and food security. These include the adoption of climate responsive agricultural techniques, embracing indigenous knowledge, implementation of the relevant legal frameworks
A thesis submitted to the University of the Witwatersrand, Johannesburg in fulfilment of the requirements for the degree of Doctor of Philosophy in the Department of Geography and Environmental Studies, 2020